Factors affecting independent audit committee member's effectiveness - the case of listed firms on Bursa Malaysia - Mohd Saat, Nur Ashikin; Karbhari, Yusuf; Xiao, Jason Zezhong; Heravi, Saed (2010)
Studies on audit committee effectiveness have so far examine the relationship between significant presence of independent directors and the establishment of influential independent stance on the committee’s decision making. However, independent composition does not ensure that audit committee members would be able to perform its financial oversight duties competently. This paper aims to investigate the characteristics of audit committee members in 221 listed firms in Bursa Malaysia. The results show that audit committee governing enhanced firm performance when there is high proportion of independent audit committee members with practicing accountant experience and firm disclosed the right of the audit committee to report to the Stock Exchange of any firm breaching of the Exchange and other regulatory rules. On the contrary, the relationship between composition of audit committee wholly by independent director and the independent committee members meeting with the external auditor without the presence of executive officers, and firm performance is negative. Notably the, collective commitment of audit committee members to fulfill their oversight duties responsibly and the sufficient co-operation of management in supplying required information to ensure effective audit committee decision-making are crucial to its effectiveness.